HEAVY METAL POLLUTION HISTORY IN THE SEDIMENTS FROM CANDARLI GULF OF TURKEY - (:unkn) unknown (Севастополь: ЭКОСИ-Гидрофизика, 2016)
Sediments are historical natural archive of environmental changes, and accurate sediment dating provides a chronology of these changes. In particular, 210Pb is the most common and reliable method during more than 5 decades, through dating of undisturbed sediment cores, to study ecosystem changes during the last 100 yrs. Meanwhile, it is common practice to use 137Cs as an independent age control to verify 210Pb method. Candarlı Gulf is one of the major industrial regions on the Aegean side of Turkey. Hence the study is dealing with the determination of the sedimentation rates and heavy metal pollution history in the sediments from Candarlı Gulf (including Aliaga Bay) derived from 210Pb and 137Cs chronology. The results were provided a realistic picture of the environmental changes of the Candarli Gulf.
ЗАГРЯЗНЕНИЕ ТЯЖЕЛЫМИ МЕТАЛЛАМИ ДОННЫХ ОСАДКОВ ЗАЛИВА ЧАНДАРЛЫ, ТУРЦИЯ
Донные осадки являются природной летописью изменений среды, и их точная датировка обеспечивает хронологию процесса. В частности, датировка ненарушенного керна с помощью 210Pb является наиболее широко используемым и надежным методом для изучения изменений в экосистемах за последние 100 лет. Также часто для независимого контроля и проверки 210Pb-метода используется 137Cs-метод. Залив Кандарли – один из важнейших индустриальных регионов на побережье Эгейского моря в Турции. Таким образом, целью работы было исследование истории загрязнения тяжелыми металлами и определение их содержания в морских грунтах залива Кандарли (включая бухту Алиага) с помощью хронологии 210Pb и 137Cs. Результаты обеспечивают достоверную картину изменений среды в заливе Кандарли.
Keywords: 210Pb; 137Cs; sediments; Candarli Gulf; pollution